Advances in the regulation of macrophage polarization by the tumor microenvironment - Minzhi Peng; Yuan Zhu; Yi Hu; Jianping Wen; Weiguo Huang (Discover Oncology)
Abstract The tumor microenvironment (Tumor Microenvironment, TME) is a core regulatory factor in the occurrence, development, and treatment resistance of tumors. Macrophages, as key immune cell components in the TME, have a profound impact on the tumor process (Visser and Joyce in Cancer Cell 41:374–403, 2023). This review aims to systematically elucidate the characteristics and functional differences of macrophage polarization into M1 and M2 phenotypes within the TME. Additionally, it endeavors to dissect the regulatory mechanisms by which metabolic products, cytokines, and extracellular matrix components secreted by tumor cells modulate macrophage polarization (Wang et al. in Mol Cancer 23:268, 2024). Moreover, the metabolic reprogramming of tumorassociated macrophage (TAM) is a core mechanism for their functional shift, and intervening in metabolic pathways holds promise for reprogramming TAMs to inhibit tumor progression (Jin et al. in Nat Cancer 6:239–252, 2025). Within the TME, macrophages can be polarized into classically activated M1 and alternatively activated M2 types (Ge and Wu in Zhongguo Fei Ai Za Zhi 26:228–237, 2023). Accumulating evidence indicates that classically activated M1 macrophages orchestrate anti-tumor immunity by secreting pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α) and interleukin-12 (IL-12), which collectively activate cytotoxic T lymphocyte responses, induce tumor cell apoptosis, and enhance immune surveillance (Luo et al. in Front Immunol 15:1352946, 2024). In contrast, M2 macrophages are induced in the TME and promote tumor angiogenesis, immune evasion, tumor cell proliferation, and metastasis by secreting factors such as vascular endothelial growth factor (VEGF) and transforming growth factor-beta (TGF-β) (Wang et al. in NPJ Precis Oncol 8:31, 2024). Therefore, in-depth research on the mechanisms of macrophage polarization in the tumor microenvironment provides an important basis for developing new tumor immunotherapy strategies and has significant clinical translational value.